(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Fiber Reinforced Concrete (FRC) is a composite material that integrates fibers into conventional concrete to improve tensile strength, reducing reliance on steel reinforcement. The fibers can be made from various materials, including natural options like coconut fiber, which is favored for its cost-effectiveness, availability, and environmental benefits, supporting sustainable construction practices. This study investigates the effect of coconut fiber reinforcement on the mechanical properties of M25 grade concrete, focusing on compressive strength, split tensile strength, and flexural strength. Concrete specimens were prepared with varying coconut fiber content at 0%, 0.5%, 1%, 1.5%, and 2% by weight of cement and tested at timing of 7, 14, and 28 days. The experimental results indicate that incorporating coconut fibers improves the mechanical performance of concrete to an optimal level. At 28 days, compressive strength increased from 38.87 MPa (control mix) to 43.73 MPa at 1% fiber content. Similarly, flexural strength improved from 3.46 MPa to 4.80 MPa, and split tensile strength increased from 3.10 MPa to 3.39 MPa at the same optimum percentage. Beyond 1% fiber content, strength declined, indicating reduced workability and fiber dispersion issues at higher dosages. Finally, the findings suggest that Coconut Fiber Reinforced Concrete offers improved mechanical properties and is a sustainable, cost-effective alternative construction material, particularly when optimised at around 1% fiber content.